Cumulative Effects of Thyroid Hormones Over 10 Years and Risk of General and Abdominal Obesity - Mehran, Ladan; Amouzegar, Atieh; Gharibzadeh, Safoora; Abdi, Hengameh; Mansournia, Mohammad Ali; Tohidi, Maryam; Azizi, Fereidoun (Hormone and Metabolic Research, 2021)
We aimed to assess if changes in thyrotropin (TSH) and free thyroxine (FT4) over 10 years of follow-up would be associated with changes in body mass index (BMI) and waist circumference (WC) or risk of obesity. We enrolled 2317 out of 4179 participants in Tehran Thyroid Study with serum TSH between 0.1–10 mU/l and without history of thyroid medication or surgery. Serum concentrations of FT4 and TSH were measured at baseline and three follow-ups (1999–2011). To account for within-subject correlation, the generalized estimating equation was used to assess the association between one standard deviation(SD) change in the main exposures [cumulative excess (CE)TSH and CEFT4] and changes in BMI and WC; calculated scores of CETSH and CEFT4 were included in models as time-varying exposures. Cumulative excess of TSH or FT4 was not associated with increased incidence of general or abdominal obesity. However, CEFT4 was negatively associated with BMI only in overweight and obese subjects. In GEE analysis, one unit increase in TSH was associated with 0.02 kg/m2 increase in BMI (95% CI: 0.01, 0.03), which remained significant only in women; although the association was not significant after adding FT4 to model. One unit increase in FT4 was associated with 1.5 kg/m2 decrease in BMI (95% CI:−1.8,−1.2) and 4.1 cm decrease in WC (95% CI:−5.1,−3.1) in both sexes independent of TSH and other confounders. Cumulative excess of TSH or FT4 indicated no risk for general or abdominal obesity. However, FT4 was negatively associated with BMI and WC independent of TSH.
Keywords: thyroid; obesity; overweight; thyroxine; thyroid stimulating hormone